2014
DOI: 10.1051/0004-6361/201322301
|View full text |Cite
|
Sign up to set email alerts
|

A mass threshold in the number density of passive galaxies atz~ 2

Abstract: The process that quenched star formation in galaxies at intermediate and high redshifts is still the subject of considerable debate. One way to investigate this puzzling issue is to study the number density of quiescent galaxies at z 2 and its dependence on mass. Here we present the results of a new study based on very deep K s -band imaging (with the HAWK-I instrument on the VLT) of two HST CANDELS fields (the UKIDSS Ultra-deep survey (UDS) field and GOODS-South). The new HAWK-I data (taken as part of the HUG… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 50 publications
2
9
0
Order By: Relevance
“…Indeed, we obtain that quiescent sources constitute only ∼ 10% of these galaxies at z = 2 − 6, which suggests that star-formation quenching and evolution into quiescence is a much slower process among intermediate-mass galaxies than among massive ones. Our findings are consistent with the results of Sommariva et al (2014), who reported a decline in the fraction of quiescent galaxies at faint near-IR magnitudes, corresponding to stellar masses < ∼ 10 10.8 M .…”
Section: Intermediate-mass Galaxiessupporting
confidence: 93%
“…Indeed, we obtain that quiescent sources constitute only ∼ 10% of these galaxies at z = 2 − 6, which suggests that star-formation quenching and evolution into quiescence is a much slower process among intermediate-mass galaxies than among massive ones. Our findings are consistent with the results of Sommariva et al (2014), who reported a decline in the fraction of quiescent galaxies at faint near-IR magnitudes, corresponding to stellar masses < ∼ 10 10.8 M .…”
Section: Intermediate-mass Galaxiessupporting
confidence: 93%
“…For both star-forming and passive galaxies, our results are in good agreement with the recent BzK number counts of McCracken et al (2010) and Sommariva et al (2014), as shown in Fig. 5.…”
Section: Number Countssupporting
confidence: 91%
“…Blue symbols represent gzK galaxies that were classified as star-forming, red symbols are for passive galaxies, orange for low-redshift galaxies and cyan for stars, classified as described in the text. Spectroscopy, along with morphological studies, support the validity of BzK-selected passive and star-forming galaxies (Daddi et al 2004(Daddi et al , 2005Ravindranath et al 2007;Hayashi et al 2009;Onodera et al 2010;Mancini et al 2010), and the simplicity and relative frugality of the technique (only three passbands are needed) continues to make it a popular choice for selecting star-forming and quiescent samples of distant galaxies (e.g., McCracken et al 2010;Furusawa et al 2011;Yuma et al 2011;Kurczynski et al 2012;McCracken et al 2012;Yuma et al 2012;Lee et al 2013;Rangel et al 2013;Sommariva et al 2014;Fang et al 2015;Ishikawa et al 2015Ishikawa et al , 2016. In Arcila-Osejo & Sawicki (2013) we adapted the classic BzK technique to the gzK s bandbasses available in CFHTLS fields by noting how the Daddi et al (2004) spectral synthesis models shift when redrawn in the g−z vs. z−K s plane (the shifts are small given the similarity of the filter sets).…”
Section: High-z Object Selection and Number Countsmentioning
confidence: 99%
“…sSFR< 10 −11 yr −1 ). For this reason, in an attempt to define a safe area for passively evolving galaxies, both the (rest-frame) UV J and the (observed) BzK diagrams adopt models in which the passive phase is well established and has been lasting for at least 1 Gyr, as we extensively discuss below (see also Sommariva et al 2014). These models can adequately describe the SFH of passively evolving galaxies even at redshifts z 2 − 3, with τ ≤ 0.5 Gyr; however, this requirement becomes difficult to match at high redshifts.…”
Section: The τ-Modelsmentioning
confidence: 99%